PENGARUH AGRESIVITAS PAJAK DAN PROFITABILITAS TERHADAP CORPORATE SOCIAL RESPONSIBILITY (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2017) - Dimas Ario Wicaksono; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2021)
The purpose of this research is to examine the influence of tax aggressiveness and profitability with corporate social responsibility. Independent variabel used in this research is the tax aggressiveness, size and profitability. Dependent variabel in this research is corporate social responsibility. This research population was manufacture companies listed on Indonesian Stock Exchange during 2016-2017. The sample of the research is chosen by using purposive sampling method. Total samples used in this study as many as 185 companies. Data then analyzed using ordinary least square regression. This research showed that the aggressiveness of corporate taxes and profitability significantly and not positively related to CSR. This result not accordance with legitimacy theory.